Balancing the Potential Gauging Process Applied to Wave Propagation for Arbitrary Space-Times - Thomas Reum (IEEE Open Journal of Antennas and Propagation)
This article addresses possibilities to compensate an unwanted side effect arising in the widely used gauging process of electrodynamic potentials due to mathematical conditions applied to describe propagating electromagnetic (EM) waves with a focus on radio frequency (RF). Previous studies have shown by means of guided propagation that phase velocities which differ from intuitive understanding occur for several components of potentials when deviating from a specific gauge determined by physical relationships. Two solution strategies are provided in a way that the changed temporal behavior of affected potentials is balanced directly or by adapted spatial relations. In this regard, appropriate changes of the metric are suitable since the choice of gauge is closely related to the space-time of a model. For this purpose, only the metric tensor of affected potential components is modified throughout this work. In contrast, that of all other EM quantities is entirely unchanged. Special relativity including a practical waveguide example in RF engineering as well as general relativity are involved to cover an extensive class of uses valid for an arbitrary choice of space-time, which assures in addition broad applicability to further physical disciplines.